Integrated Reality Theory (IRT) as a Processual-Relational Integrative Framework: Synthesis, Novelties, and Methodological Implications - M Shoim; Siti Mujanah; Abdul Halik (Journal of Finance, Economics and Business, 2026)
This article examines Integrated Reality Theory (IRT) as a cross-disciplinary synthesis effort to answer the fragmentation of modern knowledge. With a conceptual-comparative approach, this article puts IRT in dialogue with critical realism, general systems theory, and the science of complexity. The results of the analysis show that IRT has novelty in integrating processual ontology, relationalism, critical realism, and the formalization of five main variables—energy, information, entropy, consciousness, and evolution—into a dynamic model that is operational. However, the validity of constructs, especially on the variables of consciousness and evolution, is still a major challenge. This article concludes that IRT has the potential to be a useful analytical framework for the study of states, organizations, and social change, but it still requires further empirical testing.